A unified model of density limit in fusion plasmas. (21st March 2017) - Zanca, P.; Sattin, F.; Escande, D.F.; Pucella, G.; Tudisco, O.
Abstract: In this work we identify by analytical and numerical means the conditions for the existence of a magnetic and thermal equilibrium of a cylindrical plasma, in the presence of Ohmic and/or additional power sources, heat conduction and radiation losses by light impurities. The boundary defining the solutions' space having realistic temperature profile with small edge value takes mathematically the form of a density limit (DL). Compared to previous similar analyses the present work benefits from dealing with a more accurate set of equations. This refinement is elementary, but decisive, since it discloses a tenuous dependence of the DL on the thermal transport for configurations with an applied electric field. Thanks to this property, the DL scaling law is recovered almost identical for two largely different devices such as the ohmic tokamak and the reversed field pinch. In particular, they have in common a Greenwald scaling, linearly depending on the plasma current, quantitatively consistent with experimental results. In the tokamak case the DL dependence on any additional heating approximately follows a 0.5 power law, which is compatible with L-mode experiments. For a purely externally heated configuration, taken as a cylindrical approximation of the stellarator, the DL dependence on transport is found stronger. By adopting suitable transport models, DL takes on a Sudo-like form, in fair agreement with LHD experiments. Overall, the model provides a good zeroth-order quantitative description of the DL, applicable to widely different configurations.